Comparative study of thoracolumbar fascia changes in weightlifters with and without low back pain - Emma Feng Ming Zhou; Carmelo Pirri; Xiaoxiao Zhao; Juhua Peng; Tao Wen; Jianhui Fang; Chufeng Zhou; Siu Ngor Fu; Carla Stecco (PLoS ONE, 2025)
Background Thoracolumbar fascia (TLF) is thought to be linked to low back pain (LBP). This cross-sectional study aimed to investigate the difference in TLF thickness and stiffness between elite weightlifters with and without chronic LBP. Methods Forty-six elite weightlifters (aged 16–26 years; 23 with chronic bilateral LBP) were recruited. TLF thickness was measured in all participants, while stiffness was assessed in 17 of them (aged 19–25 years; 9 with chronic bilateral LBP). Investigations were conducted at the L3 level, about 2 cm lateral to midline, using ultrasound. Bright mode and shear wave elastography (SWE) mode were employed to measure the thickness and Young’s modulus (as an indicator of stiffness) of TLF, respectively. Analyses of covariates (ANCOVAs) were employed to compare the differences in TLF thickness and stiffness between LBP and non-LBP groups, controlling for pre-determined confounding factors. Repeated ANCOVAs were performed to investigate the side-to-side differences in TLF thickness and stiffness in weightlifters with and without LBP. The significance level was set as p ≤ 0.05. Results The mean thickness and stiffness of TLF were 1.63 ± 0.38 mm and 47.77 ± 13.26 kPa on the dominant, and 1.88 ± 0.60 mm and 48.09 ± 12.62 kPa on the non-dominant sides respectively. The stiffness of the TLF on the dominant side was 42.4% higher in the LBP group compared to the non-LBP control (mean difference (MD) =16.55 kPa > MDC 95 , p = 0.005, Cohen’s d = 1.58). No significant differences were detected in TLF thickness ( p > 0.05). Additionally, LBP was found to be a factor influencing the side-to-side differences in stiffness but not in thickness. Specifically, the thickness of the non-dominant side was 15.3% higher than the dominant side (MD = 0.25 mm > MDC 95 , p < 0.001, Cohen’s d = 0.63), which was not detected in stiffness. Conclusion Chronic LBP in elite weightlifters was associated with significantly higher TLF stiffness but unchanged thickness, suggesting stiffness is a more informative indicator of TLF health than thickness. Addressing stiffness in prevention and rehabilitation programs may improve weightlifters’ performance and career longevity.